2003
DOI: 10.2337/diabetes.52.8.2083
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol Elevations Comparable to Those That Occur During Hypoglycemia Do Not Cause Hypoglycemia-Associated Autonomic Failure

Abstract: The concept of hypoglycemia-associated autonomic failure (HAAF) in diabetes posits that recent antecedent iatrogenic hypoglycemia causes both defective glucose counterregulation (by reducing the epinephrine response in the setting of an absent glucagon response) and hypoglycemia unawareness (by reducing the autonomic-sympathetic neural and adrenomedullary response and the resulting neurogenic [autonomic] symptom responses) and thus causes a vicious cycle of recurrent hypoglycemia. To assess the suggestion that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…We believe that the contrasting conclusions of earlier glucocorticoid infusion studies may be related to the dose of steroid administered. While supraphysiologic hypercortisolemia (as achieved by McGregor et al [17]) may play a role in modulating sympathoadrenal responses to hypoglycemia, more moderate cortisol elevations (as achieved by Raju et al [18] and by our hydrocortisone infusion study, with cortisol responses closer to those typically observed during hypoglycemia) do not appear to exert a similar effect.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…We believe that the contrasting conclusions of earlier glucocorticoid infusion studies may be related to the dose of steroid administered. While supraphysiologic hypercortisolemia (as achieved by McGregor et al [17]) may play a role in modulating sympathoadrenal responses to hypoglycemia, more moderate cortisol elevations (as achieved by Raju et al [18] and by our hydrocortisone infusion study, with cortisol responses closer to those typically observed during hypoglycemia) do not appear to exert a similar effect.…”
Section: Discussionmentioning
confidence: 47%
“…Recent studies in human subjects have also challenged the cortisol hypothesis. In 2003, Raju et al (18) found that lowerdose cortisol infusions (1.0 -1.4 g ⅐ kg Ϫ1 ⅐ min Ϫ1 , or ϳ4 -6 mg/h) on day 1 had no effect upon day 2 sympathoadrenal responses to hypoglycemia. Our hydrocortisone infusion study results are consistent with those of Raju et al In our hands, low-dose day 1 hydrocortisone infusions (averaging 5 mg/h) had no effect upon day 2 sympathoadrenal responses to hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the relevance of the phenomenon to the pathogenesis of HAAF has been questioned. Using an experimental design generally similar to that initially used by Davis et al (68) but with lower cortisol infusion doses, we found that cortisol elevations comparable to, indeed somewhat above, those that occur during hypoglycemia (ϳ26 g/dl) did not reduce the adrenomedullary or neurogenic symptom responses to hypoglycemia the following day in healthy individuals (71). Furthermore, an adrenocortical glucocorticoid response does not appear to be critical to the effect of antecedent hypoglycemia.…”
Section: The Mechanism Of the Shift Of The Glycemic Thresholds For Symentioning
confidence: 67%
“…Another lab demonstrated cortisol-induced suppression of responses to hypoglycemia in human patients treated with high doses of adrenocorticotropic hormone to produce pharmacological cortisol levels (McGregor, Banarer, & Cryer, 2002). However, treatment with elevated levels of cortisol in the range normally measured during hypoglycemia did not reduce hypoglycemia-induced epinephrine secretion in a follow-up study (Raju, McGregor, & Cryer, 2003). Failure of glucocorticoid pretreatment to suppress responses to subsequent hypoglycemia has been reported in rodent studies.…”
Section: Construct Validity Of Rodent Haaf Modelsmentioning
confidence: 98%